Flood Hazard Mapping Using Fractal Dimension of Drainage Network in Hamadan City, Iran. Issue 4 (8th November 2017) - Malekinezhad, Hossein; Talebi, Ali; Ilderomi, Ali Reza; Hosseini, Seyed Zeynalabedin; Sepehri, Mehdi
Abstract : Recently A large number of cities in the province of Hamadan in Iran have been recently affected by several storm-flood events, causing hundreds of people to be evacuated from their homes. One of the reasons, which has markedly increased the flood hazard magnitude in the city of Hamadan relates to the suburban basins in the upper areas of the study area. In relation to the flood hazard and the priority of the suburban basins, the correlation between the geomorphological characteristics of the river system and the probability of flooding was primarily investigated. In order to assess the geomorphological characteristics of the river system and evaluate the relationship with the flooding for 5 suburban basins and also, in order to measure the accuracy of the fractal dimension in flood hazard and the priority, the SCS method was employed. The comparative results of the two employed methods demonstrated nearly the same outcome. In the fractal dimension, suburban 2 and 3 showed the maximum and minimum fractal dimensions, respectively. In the SCS method, these two suburban basins exhibited, respectively, the maximum and minimum flood hazard values. In addition, suburban 4 and 5 revealed virtually the same fractal dimension.